A cardboard castle? : an inside history of the Warsaw Pact, 1955-1991 - Mastny, Vojtech, 1936-; Byrne, Malcolm (National Security Archive Cold War readers., 2005)
This is the first book to document, analyze, and interpret the history of the Warsaw Pact based on the archives of the alliance itself. As suggested by the title, the Soviet bloc military machine that held the West in awe for most of the Cold War does not appear from the inside as formidable as outsiders often believed, nor were its strengths and weaknesses the same at different times in its surprisingly long history, extending for almost half a century. The introductory study by Mastny assesses the controversial origins of the "superfluous" alliance, its subsequent search for a purpose, its crisis and consolidation despite congenital weaknesses, as well as its unexpected demise. Most of the 193 documents included in the book were top secret and have only recently been obtained from Eastern European archives by the PHP project. The majority of the documents were translated specifically for this volume and have never appeared in English before. The introductory remarks to individual documents by co-editor Byrne explain the particular significance of each item. A chronology of the main events in the history of the Warsaw Pact, a list of its leading officials, a selective multilingual bibliography, and an analytical index add to the importance of a publication that sets the new standard as a reference work on the subject and facilitate its use by both students and general readers